Profil Peternak Sapi Perah Rakyat Tergolong Maju dan Keberhasilan Usahanya (Suatu Kasus di Tempat Pelayanan Koperasi Los Cimaung Desa Margamukti Kecamatan Pangalengan Kabupaten Bandung) - Yunasaf, Unang; Sulistyati, Marina; Nurlina, Lilis; Alim, Syahirul; Mauludin, M. Ali (Universitas Galuh, 2026)
The study was conducted at the Los Cimaung Cooperative Service Center (TPK) in Margamukti Village, Pangalengan District, Bandung Regency. The purpose of the study was to study the personal and entrepreneurial characteristics of advanced dairy farmers and the success of their dairy businesses. The study was conducted using a descriptive approach. The selection of informants was carried out purposively, totaling 12 people. The results showed that the profile of advanced dairy farmers in terms of their personal characteristics, were of productive age, had sufficient experience of over 15 years, and participated in extension and training activities. From their entrepreneurial characteristics, the informant dairy farmers showed a high orientation in achieving success from their dairy businesses and their courage in taking risks. The success of the informant's dairy business was evident in the increase in assets such as the continued increase in dairy cattle ownership and the utilization of the results to improve the quality of their welfare. Factors that need to be considered to develop advanced dairy farmers need to be done through a process of behavioral change through non-formal educational activities in the form of extension and training as well as the provision of support for affordable production inputs and milk price incentives.